KEPEMIMPINAN SANG WALIKOTA: NGAYOMI, NGAYEMI, LAN NGAYAHI (STUDI KASUS PADA KEPEMIMPINAN WALIKOTA SEMARANG, HENDRAR PRIHADI, SE.,MM.) - Purba, Jackson Roni; Darmastuti, Ismi (Diponegoro Journal of Management, 2015)
The objective of this study purposed to understand leadership of Hendrar Prihadi and analyze leadership effectiveness what he has applied in period of his position as Semarang City Major.. This research is qualitative study by exploring data from respondents who have chosen using purposive sampling methode. Source of data in this study taken from Hendrar Prihadi, his family, household affair adjudants, private drivers, and three Semarang citizens.Character and his leadership concept are able to adapted with some javanese concepts, that’s are: Hasta Brata, Ki Hajar Dewantara dan Sultan Agung. These concept also suitable with western style leadership, transformational leadership, so Hendrar Prihadi’s concept of leadership defined in seloka or javanese idiom Ngayomi (protecting), Ngayemi (reassuring) lan Ngayahi (completing all task).Application of Hendrar Prihadi’s leadership concept is effectively proven and apreciated by Municipality of Semarang officer and residents, for future days Municipality of Semarang Goverment keep leadership style that adopted from cultural reality in Semarang also has well considered by citizens and hopefully evaluate all recent shortcomings.